Nuclear Architecture in the Nervous System: Development, Function, and Neurodevelopmental Diseases - Ito, Kenji; Takizawa, Takumi (Frontiers in Genetics, 2018)
Decades of study have shown that epigenetic regulation plays an important role in neural development and function. Several layers of epigenetic mechanisms control functions of the eukaryotic cell nucleus, a well-organized subcellular organelle with distinct compartments: chromatin, its related architectural proteins, and nuclear bodies. As these components function together in the epigenetic regulation of cellular development and functions, they are collectively termed nuclear architecture. In the nervous system, dynamic rearrangement of nuclear architecture correlates with alteration of transcription programs. During maturation and upon depolarization, neurons undergo a reorganization of nuclear architecture that alters gene expression programs. As such changes allow for specialized functions, including learning and memory, nuclear architecture is distinct among cell types. Studying nuclear architecture of neurons may uncover cell-division-independent mechanisms of global and local changes to nuclear architecture. We herein review recent research concerning nuclear architecture in the nervous system and will discuss its importance to the development, maturation, function, and diseases of the nervous system.